Proximity labelling of pro-interleukin-1α reveals evolutionary conserved nuclear interactions - Rose Wellens; Victor S. Tapia; Paula I. Seoane; Hayley Bennett; Antony Adamson; Graham Coutts; Jack Rivers-Auty; Martin Lowe; Jack P. Green; Gloria Lopez-Castejon; David Brough; Christopher Hoyle (Nature Communications, 2024)
Abstract Interleukin-1α is a suggested dual-function cytokine that diverged from interleukin-1β in mammals potentially by acquiring additional biological roles that relate to highly conserved regions in the pro-domain of interleukin-1α, including a nuclear localisation sequence and histone acetyltransferase-binding domains. Why evolution modified pro-interleukin-1α’s subcellular location and protein interactome, and how this shaped interleukin-1α’s intracellular role, is unknown. Here we show that TurboID proximity labelling with pro-interleukin-1α suggests a nuclear role for pro-interleukin-1α that involves interaction with histone acetyltransferases, including EP300. We also identify and validate inactivating mutations in the pro-interleukin-1α nuclear localisation sequence of multiple mammalian species, including toothed whales, castorimorpha and marsupials. However, histone acetyltransferase-binding domains are conserved in those species that have lost pro-interleukin-1α nuclear localisation. Together, these data suggest that histone acetyltransferase binding and nuclear localisation occurred together, and that while some species lost the nuclear localisation sequence in their pro-interleukin-1α, histone acetyltransferase binding ability was maintained. The nuclear localisation sequence was lost from several distinct species at different evolutionary times, suggesting convergent evolution, and that the loss of the nuclear localisation sequence confers some important biological outcome.